Spectroscopic discrimination of non-stunned and electrically stunned chicken meat using portable NIR spectroscopy and predictive modeling - Nayeem Mia; Md Ab Rahman; Md. Abul Hashem; Md. Mukhlesur Rahman; Md. Shawkat Ali (Food and Humanity, 2026)

Spatiotemporal impact of thermal and drought stress on vegetation in the Yangtze River Delta using remote sensing imagery data and machine learning models - Abdul Basit; Wilson Kalisa; Amina Gul; Shawkat Ali; Hidayat Ullah; Jiahua Zhang (Advances in Space Research, 2026)

Assessing vegetation trends and land degradation in a typical semi-arid region: insights from the sustainable development goal 15.3.1 framework and remote sensing - Adeel Ahmad; Ali Salem Al-Sakkaf; Shawkat Ali; Hidayat Ullah; Barjeece Bashir; Kashif Mahmood; Jiahua Zhang (Arabian Journal of Geosciences, 2026)

RDANet: ResNeXt-based dual attention network for accurate sea and land segmentation in remote sensing image - Yanxu Zhang; Jiahua Zhang; Xuan Xiong; Xiaopeng Wang; Delong Kong; Foyez Ahmed Prodhan; Shawkat Ali; Hidayat Ullah (Regional Studies in Marine Science, 2026)

Reconstruction of the three-dimensional dissolved oxygen and its spatio-temporal variations in the Mediterranean Sea using machine learning - Guangsheng Liu; Xiang Yu; Jiahua Zhang; Xiaopeng Wang; Nuo Xu; Shawkat Ali (Journal of Environmental Sciences, 2025)

Significant spatiotemporal shifts of land cover over the Mongolian Plateau through the past three decades - Hidayat Ullah; Xue Wang; Shawkat Ali; Delong Kong; Xiaopeng Wang; Shanshan Yang; Jiahua Zhang (Science of The Total Environment, 2025)

Fine extraction of multi-crop planting area based on deep learning with Sentinel- 2 time-series data - Jingmin Jiang; Jiahua Zhang; Xue Wang; Shichao Zhang; Delong Kong; Xiaopeng Wang; Shawkat Ali; Hidayat Ullah (Environmental Science and Pollution Research, 2025)

Accurate estimation of suspended sediment concentration integrated remote sensing information and a novel stacking machine learning model - Xiaotian Fang; Jiahua Zhang; Xiang Yu; Shichao Zhang; Delong Kong; Xiaopeng Wang; Shawkat Ali; Hidayat Ullah; Nuo Xu (Stochastic Environmental Research and Risk Assessment, 2025)

Intercomparison of gross primary productivity in spatio-temporal distribution over a typical tropical region based on different datasets - Sha Zhang; Yun Bai; Jiahua Zhang; Xin Zheng; Shawkat Ali; Hidayat Ullah (Environmental Science and Pollution Research, 2024)

Global analysis of the apple fruit microbiome: are all apples the same? - Ahmed Abdelfattah; Shiri Freilich; Rotem Bartuv; V. Yeka Zhimo; Ajay Kumar; Antonio Biasi; Shoshana Salim; Oleg Feygenberg; Erik Burchard; Christopher Dardick; Jia Liu; Awais Khan; et al. (Environmental Microbiology, 2021)
Summary We present the first worldwide study on the apple ( Malus × domestica) fruit microbiome that examines questions regarding the composition and the assembly of microbial communities on and in apple fruit. Results revealed that the composition and structure of the fungal and bacterial communities associated with apple fruit vary and are highly dependent on geographical location. The study also confirmed that the spatial variation in the fungal and bacterial composition of different fruit tissues exists at a global level. Fungal diversity varied significantly in fruit harvested in different geographical locations and suggests a potential link between location and the type and rate of postharvest diseases that develop in each country. The global core microbiome of apple fruit was represented by several beneficial microbial taxa and accounted for a large fraction of the fruit microbial community. The study provides foundational information about the apple fruit microbiome that can be utilized for the development of novel approaches for the management of fruit quality and safety, as well as for reducing losses due to the establishment and proliferation of postharvest pathogens. It also lays the groundwork for studying the complex microbial interactions that occur on apple fruit surfaces.

Nexus among rice production and environmental factors in the coastal region of Bangladesh: a stochastic modeling approach for future forecasting - Md. Jakariya; Sazzadur Rahman Sarker; Sheikh Mohammad Sayem; Saman Saad; Md. Nazrul Islam; Abir Rahman; Md. Sajadul Alam; Mirza Shawkat Ali; Dilruba Akter (Modeling Earth Systems and Environment, 2021)

In Planta Transformation of Tomato - Abida Yasmeen; Bushra Mirza; Samia Inayatullah; Naila Safdar; Maryam Jamil; Shawkat Ali; M. Fayyaz Choudhry (Plant Molecular Biology Reporter, 2009)